2006
DOI: 10.1182/blood.v108.11.1051.1051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Laboratory Tests for the Diagnosis of Heparin-Induced Thrombocytopenia.

Abstract: The laboratory diagnosis of heparin-induced thrombocytopenia (HIT) relies on the demonstration of antibodies to the heparin-platelet factor 4 (H-PF4) complex. Assays are based on the functional ability of H-PF4 antibodies to activate platelets, or detect the antibody directly by immunological methods. Multiple assays in each category are currently in clinical use and newer, rapid immunological assays are becoming available. The aim of this study was to compare available methods for detecting H-PF4 antibodies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Although we cannot exclude the possibility of some unidentified technical artifact, our data, taken together with the results of the studies of Francis et al. [9], indicate that the PIFA has limited value for the diagnostic evaluation of HIT.…”
contrasting
confidence: 48%
See 2 more Smart Citations
“…Although we cannot exclude the possibility of some unidentified technical artifact, our data, taken together with the results of the studies of Francis et al. [9], indicate that the PIFA has limited value for the diagnostic evaluation of HIT.…”
contrasting
confidence: 48%
“…There is but one preliminary report by Francis et al. [9] comparing the PIFA to the GTI EIA and other assays for HIT antibodies. Although ROC curves were not presented, the authors indicated that the PIFA exhibited only a 56.7% correlation with the GTI EIA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the assays described above, the Particle Immuno Filtration assay produces considerable false negative and false positive results compared to the ELISA (86), and seem to have a poor correlation with the 4Ts score (19). The manufacturer claimes to have improved test procedures after these publications.…”
Section: Particle Gel Immunoassaymentioning
confidence: 99%